Engaging China : the management of an emerging power - Johnston, Alastair I.; Ross, Robert S., 1954- (Politics in Asia series., 1999)
In an interesting mix of the empirical and theoretical, case studies from the US, Japan, Singapore, Taiwan, Korea, Malaysia and Indonesia illustrate China's developing position in the Asia-Pacific.